Biomechanical risk factors and flexor tendon frictional work in the cadaveric carpal tunnel. Issue 3 (5th February 2015) - Kociolek, Aaron M.; Tat, Jimmy; Keir, Peter J.
Abstract Pathological changes in carpal tunnel syndrome patients include fibrosis and thickening of the subsynovial connective tissue (SSCT) adjacent to the flexor tendons in the carpal tunnel. These clinical findings suggest an etiology of excessive shear-strain force between the tendon and SSCT, underscoring the need to assess tendon gliding characteristics representative of repetitive and forceful work. A mechanical actuator moved the middle finger flexor digitorum superficialis tendon proximally and distally in eight fresh frozen cadaver arms. Eighteen experimental conditions tested the effects of three well-established biomechanical predictors of injury, including a combination of two wrist postures (0° and 30° flexion), three tendon velocities (50, 100, 150 mm/sec), and three forces (10, 20, 40 N). Tendon gliding resistance was determined with two light-weight load cells, and integrated over tendon displacement to represent tendon frictional work. During proximal tendon displacement, frictional work increased with tendon velocity (58.0% from 50–150 mm/sec). There was a significant interaction between wrist posture and tendon force. In wrist flexion, frictional work increased 93.0% between tendon forces of 10 and 40 N. In the neutral wrist posture, frictional work only increased 33.5% (from 10–40 N). During distal tendon displacement, there was a similar multiplicative interaction on tendon frictional work. Concurrent exposure to multiple biomechanical work factors markedly increased tendon frictional work, thus providing a plausible link to the pathogenesis of work-related carpal tunnel syndrome. Additionally, our study provides the conceptual basis to evaluate injury risk, including the multiplicative repercussions of combined physical exposures.